2012
DOI: 10.1186/2008-6970-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Hemolymph osmotic, ionic status, and branchial Na+/K+-ATPase activity under varying environmental conditions in the intertidal grapsid crab, Gaetice depressusd

Abstract: In the current study, ten elements contents (Fe, Zn, Mn, Cu, Cr, Co, Ni, Cd, Pb and Hg) have been measured in muscle and liver of four pelagic fish species (Engraulis encrasicolus, Sardina pilchardus, Scomber japonicus and Trachurus trachurus) from the north-west African coast (South Atlantic Moroccan coast), collected during summer and autumn seasons (July and December 2013, respectively). Significant differences in metal contents were found between the different species (p \ 0.05). Metals levels were also mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In this study, we observed significant increases in the Na + /K + -ATPase activity of gills 6 and 8 one week after acclimation to 20-ppt salinity ( Fig. 4 ), similarly to the posterior gills in many crustaceans structurally and functionally specialized as the principal site of osmoregulatory ion transport 30 37 38 40 . The involvement of other transport proteins and transport-related enzymes (e.g., a Na + /H + antiporter, carbonic anhydrase, Cl − /HCO3 − exchanger, Na + /K + /2Cl − cotransporters, and V-ATPases) and/or the acid-base balance/ammonium transport cannot be excluded 41 , but little is known about the related parameters during acclimation to different salinities.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In this study, we observed significant increases in the Na + /K + -ATPase activity of gills 6 and 8 one week after acclimation to 20-ppt salinity ( Fig. 4 ), similarly to the posterior gills in many crustaceans structurally and functionally specialized as the principal site of osmoregulatory ion transport 30 37 38 40 . The involvement of other transport proteins and transport-related enzymes (e.g., a Na + /H + antiporter, carbonic anhydrase, Cl − /HCO3 − exchanger, Na + /K + /2Cl − cotransporters, and V-ATPases) and/or the acid-base balance/ammonium transport cannot be excluded 41 , but little is known about the related parameters during acclimation to different salinities.…”
Section: Discussionsupporting
confidence: 60%
“…Slopes resulting from regression analysis between hemolymph osmotic/ionic concentrations and those in medium at given salinity have been used to determine the ability of aquatic organisms to osmo- and ionoregulate 4 5 37 38 . The closer the deviation of slope to the isosmotic and isoionic line (slope = 1), the lower the ability of the organisms to osmo- and ionoregulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The osmoregulation mechanisms for the crustacean species, however, are not well studied so far (Towle & Weihrauch 2001, Luquet et al 2005. It was also reported that the potential energy of Na + gradient could affect the Ca 2+ channel, Ca 2+ -ATPase, Na + /Ca 2+ exchanger and the Ca 2+ transportation in the hemolymph system of the crustaceans (Roer & Dillaman 1993, Nanba et al 2012). The fluctuant salinity might alter the Ca 2+ levels that might be correlated with the CacyBP protein.…”
Section: Discussionmentioning
confidence: 96%
“…Salinity is an important factor affecting osmoregulation in S. paramamosain (Wang, Tang, Wei, Lu, Mu, et al, 2018; Wang, Wei, et al, 2019). Ion concentrations (K + , Cl ‐ and Na + ) and Na + /K + ‐ATPase activity are important indicators reflecting osmoregulation ability (Geng, Tian, et al, 2016; Geng, Tong, Jiang, & Xu, 2016; Nanba et al., 2012).…”
Section: Discussionmentioning
confidence: 99%